Brachial Tunneled Peripherally Inserted Central Catheters and the Risk of Catheter Complications: A Systematic Review and Meta-Analysis - Davide Giustivi; Mattia Donadoni; Stefano Maria Elli; Francesco Casella; Massimiliano Quici; Chiara Cogliati; Silvia Cavalli; Giulia Rizzi; Leyla La Cava; Arianna Bartoli; Elena Martini; Alba Taino; et al. (MDPI AG, 2024)
Introduction: Situations involving increased workloads and stress (i.e., the COVID-19 pandemic) underline the need for healthcare professionals to minimize patient complications. In the field of vascular access, tunneling techniques are a possible solution. This systematic review and meta-analysis aimed to compare the effectiveness of tunneled Peripherally Inserted Central Catheters (tPICCs) to conventional Peripherally Inserted Central Catheters (cPICCs) in terms of bleeding, overall success, procedural time, and late complications. Methods: Randomized controlled trials without language restrictions were searched using PUBMED®, EMBASE®, EBSCO®, CINAHL®, and the Cochrane Controlled Clinical Trials Register from August 2022 to August 2023. Five relevant papers (1238 patients) were included. Results: There were no significant differences in overall success and nerve or artery injuries between the two groups (p = 0.62 and p = 0.62, respectively), although cPICCs caused slightly less bleeding (0.23 mL) and had shorter procedural times (2.95 min). On the other hand, tPICCs had a significantly reduced risk of overall complications (p < 0.001; RR0.41 [0.31-0.54] CI 95%), catheter-related thrombosis (p < 0.001; RR0.35 [0.20-0.59] IC 95%), infection-triggering catheter removal (p < 0.001; RR0.33 [0.18-0.61] IC 95%), wound oozing (p < 0.001; RR0.49 [0.37-0.64] IC 95%), and dislodgement (p < 0.001; RR0.4 [0.31-0.54] CI 95%). Conclusions: The tunneling technique for brachial access appears to be safe concerning intra-procedural bleeding, overall success, and procedural time, and it is effective in reducing the risk of late complications associated with catheterization.